Post-Covid-19 Learning: Problem-Based Learning and Its Effect on Critical Thinking Skills - Linda Tri Antika; Rofiqi Rofiqi; Akhmad Fathir; Moch. Haikal (Bioedusiana: Jurnal Pendidikan Biologi, 2022)
MA Miftahul Ulum Nagasari Congkop Tlambah Karang Penang Sampang Madura is one of the schools in Madura, which still showed the condition of students who were not accustomed to high-level thinking, including critical thinking skills, so that it had an impact on learning outcomes that were not optimal. This study aimed to determine the effect of PBL on critical thinking skills. The subjects of this study were students of class X A IPA and class X B IPA at MA Miftahul Ulum Nagasari Congkop Tlambah Karang Penang Sampang in the second semester of academic year2021/2022. This research is quantitative research with a quasi-experimental type. This research design used a non-equivalent pretest-posttest control group research design. Critical thinking skills were measured using the critical thinking skills rubric, where critical thinking skills scoring was integrated with a written test. The technical analysis used was Quade's Rank with SPSS 28.00. The results of this study indicated that there was an effect of the PBL learning model on students' critical thinking skills. The effect size of PBL on students' critical thinking skills was 0.289.